The bluestocking salons of eighteenth-century Britain - Hasan, Md. Mahmudul (2018)
While pre-eighteenth-century British women writers mingled among acquaintances in what Margaret Ezell terms “coterie circles”, bluestocking women made one step ahead. They enjoyed a greater space and their gender-neutral gatherings placed them on a complementary equivalence with men in literary discussions. Emphasizing this aspect of bluestocking intellectual life, Bridget Hill, in Eighteenth-century Women: An Anthology, states that bluestocking women “not only insisted on their ability to converse on equal terms with men, but in their salons demonstrated such ability and received public recognition for their intellectual attainments and their conversational wit.”